Developing emotional intelligence in a static and interactive music learning environment - Liang, Jitao (Frontiers in Psychology, 2024)
The concept of a static electronic learning environment implies the utilization of tools that do not necessitate any active participation on the part of the learner aside from familiarizing oneself with the provided materials. In contrast, an interactive electronic learning environment necessitates active engagement and interaction from the learner. The research purpose is to compare the impact of interactive and static learning environments on students' emotional intelligence. Music education students (n=216) took a theoretical course on emotional intelligence during one academic semester at the university. The students were randomly divided into two equal groups: Group A (n=108) attended the course in a lecture format, using videos and additional reading materials. Group B participated in online forums, completed interactive exercises, and discussed individual personal diaries kept at home with the teacher. At the end of the semester, both groups completed the Mayer-Salovey-Caruso emotional intelligence test. The results suggest that the total score for emotional intelligence was higher in Group B. After another 6 months of training, students passed the same test again to assess the effectiveness of the long-term intervention strategy. The post-training results suggest that Group B has an advantage in training over Group A. At the same time, in the Managing Emotions subcategory, Group B was behind Group A, but after six months of training, Group B significantly improved the results (p-value = 0.01 ). The research summarizes the practical significance of the theoretical course on the development of emotional intelligence among music education students.